Eating behavior and stress: a pathway to obesity - Sominsky, Luba; Spencer, Sarah J. (Frontiers in Psychology, 2014)
Stress causes or contributes to a huge variety of diseases and disorders. Recent evidence suggests obesity and other eating-related disorders may be among these. Immediately after a stressful event is experienced, there is a corticotropin-releasing-hormone (CRH)-mediated suppression of food intake. This diverts the body’s resources away from the less pressing need to find and consume food, prioritizing fight, flight, or withdrawal behaviours so the stressful event can be dealt with. In the hours following this, however, there is a glucocorticoid-mediated stimulation of hunger and eating behaviour. In the case of an acute stress that requires a physical response, such as a predator-prey interaction, this hypothalamic-pituitary-adrenal (HPA) axis modulation of food intake allows the stressful event to be dealt with and the energy used to be replaced afterwards. In the case of ongoing psychological stress, however, chronically elevated glucocorticoids can lead to chronically stimulated eating behaviour and excessive weight gain. In particular, stress can enhance the propensity to eat high calorie “palatable” food via its interaction with central reward pathways. Activation of this circuitry can also interact with the HPA axis to suppress its further activation, meaning not only can stress encourage eating behaviour, but eating can suppress the HPA axis and the feeling of stress. In this review we will explore the theme of eating behaviour and stress and how these can modulate one another. We will address the interactions between the HPA axis and eating, introducing a potential integrative role for the orexigenic hormone, ghrelin. We will also examine early life and epigenetic modulation of the HPA axis and how this can influence eating behaviour. Finally, we will investigate the clinical implications of changes to HPA axis function and how this may be contributing to obesity in our society.